The role of art in developing creativity in children at childhood education: what do teachers think and do (Revista Educação, Artes e Inclusão, 2022)
Creativity develops in the social and cultural context, characterized as instruments of expression, understanding of the self and the collective. Throughout the 20th century, the role of creativity in education gained prominence, due to constant social, cultural and technological changes, and found in art means for its development. So, what do teachers think and do about the students' creativity? To answer this question, the objective of the research is to analyze the conceptions and actions that provide the development of creativity, focusing on Early Childhood Education students. The present research is characterized in a field study, from indirect observation, and uses as a data collection instrument the face-to-face, semi-structured interview, with questions regarding the knowledge of the concepts and practices of creativity with teachers from five Kindergarten schools. The results pointed out reaffirm art as the component that has the greatest possibility of developing creativity, highlighting the need for initial teacher training to be directed towards enabling the creative performance of their profession, as well as the constant need for search, breaking with paradigms and stereotypes, and cultivating creativity at school.
Keywords: Creativity; Childhood Education; Practical teaching; Art-Education